PTH-092 N-acetylcysteine and prednisolone combination therapy in severe alcoholic hepatitis, an NHS teaching hospital pilot study. (8th June 2018) - Griffiths, Joshua; Al-Joudeh, Amer
Abstract : Introduction: Severe Alcoholic Hepatitis (AH) (defined as a Maddray score >32) is a life-threatening condition with a recently reported 1 month mortality of 14% and 1 year mortality of 57%. The current mainstay of treatment is corticosteroid therapy, but previous studies suggest adding N-acetylcysteine (NAC) improves short-term mortality. We assess the effect on mortality of NAC as additional treatment for severe AH. Methods: We collected data using a standard proforma for patients admitted and diagnosed with severe AH (Maddray score of >32). Patients were treated with prednisolone (40 mg/day) and 5 days of IV NAC (at a dose of 150, 50, and 100 mg per kilogram of body weight in 250, 500, and 1000 ml of 5% glucose solution over a period of 30 mins, 4 hours, and 16 hours, respectively) and on days 2 through 5 (100 mg per kilogram per day in 1000 ml of 5% glucose solution). Patients were collected between 1 st of May and 30th of October. We calculated the Lille score on day 7 of treatment and continued prednisolone in responders. Analysis was on a per-protocol basis. Mortality was assessed at 1, 3 and 6 months. Results: 10 patients were included. Mortality is show in table 1 and compared to previous trials. The mean age of patients included was 51.6±11.06. Participants baseline characteristics were consistent with previous publications Maddray score 61±27.9, Bilirubin 233.6±119.3, Prothrombin time (PT) 21.1+/-5.7. Over the six months, there were 4 episodes of infection (40%) and 0 episodes of hepatorenal syndrome. After treatment the mean Lille score was 0.433±0.31. Of those patients that died there was a significant difference compared to patients who survived in initial Maddray score at 30 days (Alive: 53.4±23.2, Dead: 95.5±16.3 (p=0.041)) and at 6 months (Alive 38.6±16.1, Dead 83.4±15.4 (p=0.002)). There was no significant difference in Lille scores in patients that died at 1 or 6 months. Conclusions: Treatment with combination of NAC and corticosteroids demonstrated slightly worse outcomes compared with recent trials although our numbers are too small to be certain. This study suggests significantly elevated Maddray scores are associated with an increased risk of mortality in severe AH. We feel a larger study to validate previous data and fully assess the effect of NAC in the treatment of AH on short term mortality is needed.